Ocular Tuberculosis - Kumar, Atul.; Chawla, Rohan; Sharma, Namrata; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
A concise guide for ophthalmologists detailing tuberculosis, which can cause disease in multiple organs throughout the body, including the eye. Tuberculosis is an infection caused by Mycobacterium tuberculosis. It can affect any part of the eye (intraocular, superficial or surrounding the eye), with or without presence of systemic involvement. Difficulty in obtaining adequate ocular tissue for histopathological and microbiological analysis makes it difficult to conclusively establish a diagnosis of tuberculosis in ocular disorders. Ocular Tuberculosis is a text devoted to in-depth coverage of this topic. Written and edited by international leaders in the field, discussing detailed and practical information on everything from clinical features, ocular imaging studies, and pathology, to investigations, treatment and surgical management of this disease, Ocular Tuberculosis is a truly comprehensive text.
1.Epidemiological Aspect of Ocular Tuberculosis -- 2.Pathogenesis and Pathology of Ocular Tuberculosis -- 3.Imaging Studies for Ocular Tuberculosis -- 4.Laboratory and Radiological Investigations in Diagnosis of Ocular Tuberculosis -- 5.Tuberculin Skin Test and Interferon gc (BRelease Assays in the Diagnosis of Ocular Tuberculosis -- 6.Management of Ocular Tuberculosis -- 7.Tubercular Uveitis -- 8.Tubercular Multifocal Serpiginoid Choroiditis -- 9.Tubercular Retinitis and Retinal Vasculitis -- 10.Tubercular Optic Neuropathy -- 11.Ocular Tuberculosis in Immunocompromised Patients -- 12.Conjunctival and Corneal Tuberculosis -- 13.Tubercular Scleritis -- 14.Orbital and Periorbital Tuberculosis.s
Keywords: Medicine; Ophthalmology; Medicine & Public Health; Ophthalmology